Development of Bahiagrass Fertilization Recommendations: 1990-2008 - Edward A. Hanlon; Rao Mylavarapu; Cheryl L. Mackowiak; Maria L. Silveira (EDIS)
Revised! SL-237, a 15-page fact sheet by E.A. Hanlon, Rao Mylavarapu, C.L. Mackowiak, and M.L. Silveira, records changes in UF/IFAS’ bahiagrass fertilization and liming recommendations from 1990 through 2008 and summarizes efforts of the various work groups and committees. Includes references. Published by the UF Department of Soil and Water Science, January 2006. Revised August 2008 and April 2009.